Preschool in Rural Context: A Documentary Review of Public Policies in Chile - Mora Guerrero, Gloria Miryam (2022)
Since preschool in Chile represents a public strategy in favor of equity for children under 6 years of age in vulnerable socioeconomic conditions, as those whose family lives in rural areas, and it has relevant implications in child development, it was explored the way in which preschool policy is intended to respond to the sociocultural and geographic conditions of families in rural areas from 1990 onwards. Through a documentary review, 1664 (mostly governmental) documents were identified, and 82 were selected and analyzed. The results showed that preschool policy takes intersectoriality as a strategy for territorial pertinence, in order to strengthen education and health in early childhood, overcome poverty, and insert mothersin the labor market. Conclusions discuss the scarce clarity of the policies studied with respect to mechanisms that articulate preschool education with rural territories.